Genomic Characterization of Salmonella Isangi: A Global Perspective of a Rare Serovar - Anamaria Mota Pereira dos Santos; Pedro Panzenhagen; Rafaela G. Ferrari; Ana Carolina S. de Jesus; Ana Beatriz Portes; Alan Clavelland Ochioni; Dalia dos Prazeres Rodrigues; Carlos Adam Conte-Junior (Antibiotics, 2023)
Salmonella Isangi is an infrequent serovar that has recently been reported in several countries due to nosocomial infections. A considerable number of reports indicate Salmonella Isangi multidrug resistance, especially to cephalosporins, which could potentially pose a risk to public health worldwide. Genomic analysis is an excellent tool for monitoring the emergence of microorganisms and related factors. In this context, the aim of this study was to carry out a genomic analysis of Salmonella Isangi isolated from poultry in Brazil, and to compare it with the available genomes from the Pathogen Detection database and Sequence Read Archive. A total of 142 genomes isolated from 11 different countries were investigated. A broad distribution of extended-spectrum beta-lactamase (ESBL) genes was identified in the Salmonella Isangi genomes examined (blaCTX-M-15, blaCTX-M-2, blaDHA-1, blaNDM-1, blaOXA-10, blaOXA-1, blaOXA-48, blaSCO-1, blaSHV-5, blaTEM-131, blaTEM-1B), primarily in South Africa. Resistome analysis revealed predicted resistance to aminoglycoside, sulfonamide, macrolide, tetracycline, trimethoprim, phenicol, chloramphenicol, and quaternary ammonium. Additionally, PMQR (plasmid-mediated quinolone resistance) genes qnr19, qnrB1, and qnrS1 were identified, along with point mutations in the genes gyrAD87N, gyrAS83F, and gyrBS464F, which confer resistance to ciprofloxacin and nalidixic acid. With regard to plasmids, we identified 17 different incompatibility groups, including IncC, Col(pHAD28), IncHI2, IncHI2A, IncM2, ColpVC, Col(Ye4449), Col156, IncR, IncI1(Alpha), IncFIB (pTU3), Col(B5512), IncQ1, IncL, IncN, IncFIB(pHCM2), and IncFIB (pN55391). Phylogenetic analysis revealed five clusters grouped by sequence type and antimicrobial gene distribution. The study highlights the need for monitoring rare serovars that may become emergent due to multidrug resistance.